2021
DOI: 10.3390/pharmaceutics13070974
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Acting Zeta-Potential-Changing Micelles for Optimal Mucus Diffusion and Enhanced Cellular Uptake after Oral Delivery

Abstract: Context: Overcoming the intestinal mucosal barrier can be a challenge in drug delivery. Nanoemulsions with negative zeta potentials can effectively permeate the mucus layer, but those with positive zeta potentials are better taken up by cells; a nanoemulsion with capricious zeta potential from negative to positive can achieve both good permeation and high uptake. Objective: This study aimed to develop dual-acting zeta-potential-amphoteric micelles enabling optimal muco-permeation and enhancement of cellular up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Atomoxetine-loaded SLNs formulae containing stearic acid had significantly higher negative ZP and lower PDI than the formulae containing Compritol 888 ATO according to the ANOVA test results ( p = 0.0143 and 0.0552 for effect of lipid type (X1) on ZP and PDI, respectively). The higher negative ZP is attributed to the negative charge of stearic acid obtained from the carboxylic acid moiety oriented in the hydrophilic surface of nanoparticles [ 29 ]. As shown in Figure 4 , it was also found that using lower co-surfactant ratio of span 60: Pluronic f127 of (1:3) enhanced the stability of the formed pre-emulsion and decreased the tendency of the nanoparticles to aggregate ( p -value = 0.0053) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Atomoxetine-loaded SLNs formulae containing stearic acid had significantly higher negative ZP and lower PDI than the formulae containing Compritol 888 ATO according to the ANOVA test results ( p = 0.0143 and 0.0552 for effect of lipid type (X1) on ZP and PDI, respectively). The higher negative ZP is attributed to the negative charge of stearic acid obtained from the carboxylic acid moiety oriented in the hydrophilic surface of nanoparticles [ 29 ]. As shown in Figure 4 , it was also found that using lower co-surfactant ratio of span 60: Pluronic f127 of (1:3) enhanced the stability of the formed pre-emulsion and decreased the tendency of the nanoparticles to aggregate ( p -value = 0.0053) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, dual-acting zeta-potential micelles were designed to achieve optimal muco-permeation and cellular uptake. Through slow and time-dependent changes in zeta potentials, micellar droplets provide optimal mucus permeation and significant cellular uptake [118].…”
Section: Future Perspectivementioning
confidence: 99%
“…The intestinal mucosal barrier poses a challenge in oral drug delivery, and the development of dual-acting zeta-potential-amphoteric micelles has been proposed to overcome it, by allowing optimal mucopermeation and enhancing cellular uptake [ 7 ]. The rationale of the work is that, since the zeta potential of nanoemulsions is known to influence both parameters in opposite directions (cellular uptake is promoted by positively charged and permeation by negatively charged nanodroplets), a system capable of zeta-potential shifting would be beneficial.…”
mentioning
confidence: 99%